Tecnofagia: A Multimodal Rite - Aliel, Luzilei; Fajiolli, Rafael; Thomasi, Ricardo (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This is a concert proposal of Brazilian digital art, which brings in its creative core the historical and cultural aspects of certain locations in Brazil. The term ​ Tecnofagia derives from an allusion to the concept of anthropophagic movement (artistic movement started in the twentieth century founded and theorized by the poet Oswald de Andrade and the painter Tarsila do Amaral). The anthropophagic movement was a metaphor for a goal of cultural swallowing where foreign culture would not be denied but should not be imitated. In his notes, Oswald de Andrade proposes the "cultural devouring of imported techniques to re-elaborate them autonomously, turning them into an export product." The ​ Tecnofagia project is a collaborative creative and collective performance group that seeks to broaden aspects of live electronic music, video art, improvisation and performance, taking them into a multimodal narrative context with essentially Brazilian sound elements such as:accents and phonemes; instrumental tones; soundscapes; historical, political and cultural contexts. In this sense, ​ Tecnofagia tries to go beyond techniques and technologies of interactive performance, as it provokes glances for a Brazilian art-technological miscegenation. That is, it seeks emergent characteristics of the encounters between media, art, spaces, culture, temporalities, objects, people and technologies, at the moment of performance.